Design, Synthesis, Biological Investigations, and in Silico Studies of Sulfonate Esters of 2-(2-benzylidenehydrazono)-4-Oxothiazolidine-5-Acetic Acid as α-Glucosidase Inhibitors - Kaur R.; Kumar R.; Dogra N.; Yadav A.K. (My University, 2025)
This study reported the discovery of sulfonate ester analogues of 2-(2-benzylidenehydrazono)-4-oxothiazolidine-5-acetic acid as α-glucosidase inhibitors. Sulfonate ester analogues of 2-(2-benzylidenehydrazono)-4-oxothiazolidine-5-acetic acids were synthesized, and characterized. The synthesized compounds were evaluated for in vitro α-glucosidase inhibition and anti-oxidant activities. All synthesized derivatives exhibited significant inhibitory activities against α-glucosidase enzyme as compared to acarbose. Compound 7d emerged to be the most potent with IC50 value of 29.39 µM. Safety profile of the 7d was established by MTT assay in normal HEK cells. Further, in vivo disaccharide loading test of 7d validated the higher efficacy of 7d over acarbose at a dose of 20 mg/kg of body weight. In silico studies involving molecular docking, binding free energy calculations and ADME predictions further validated in vitro and in vivo study results. © 2025 Wiley-VCH GmbH.